2012
DOI: 10.1172/jci59816
|View full text |Cite
|
Sign up to set email alerts
|

Direct leptin action on POMC neurons regulates glucose homeostasis and hepatic insulin sensitivity in mice

Abstract: Leptin action on its receptor (LEPR) stimulates energy expenditure and reduces food intake, thereby lowering body weight. One leptin-sensitive target cell mediating these effects on energy balance is the proopiomelanocortin (POMC) neuron. Recent evidence suggests that the action of leptin on POMC neurons regulates glucose homeostasis independently of its effects on energy balance. Here, we have dissected the physiological impact of direct leptin action on POMC neurons using a mouse model in which endogenous LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
299
4
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(327 citation statements)
references
References 62 publications
15
299
4
9
Order By: Relevance
“…Previous studies have shown that insulin-mediated suppression of endogenous glucose production and stimulation of glucose disposal are identical in POMC-cre mice and their WT littermates (27). These data demonstrate that expression of the POMC-cre transgene does not independently affect clamp data.…”
Section: Figuresupporting
confidence: 55%
“…Previous studies have shown that insulin-mediated suppression of endogenous glucose production and stimulation of glucose disposal are identical in POMC-cre mice and their WT littermates (27). These data demonstrate that expression of the POMC-cre transgene does not independently affect clamp data.…”
Section: Figuresupporting
confidence: 55%
“…Selective loss of 5HT-2CR signaling in POMC neurons resulted in hyperphagia and sensitization to dietinduced obesity and blunted the effects of D-fenfluramine and mCPP to suppress eating [264]. These data support the role of POMC neurons in the arcuate nucleus in the control of eating, in contrast to the demonstration that leptin receptor signaling via POMC neurons did not affect eating, only energy expenditure [255,265]. It is important to note that 5HT-2CR and leptin receptors are expressed by anatomically and functionally distinct POMC neurons in the arcuate nucleus, but these populations converge on similar second-order neurons, including those expressing MC4R [228,229].…”
Section: Pomc Neuronsmentioning
confidence: 58%
“…It is known that leptin functions by activating leptin receptors located in the central nervous system and peripheral tissues (45,46). We therefore analyzed whether hLeptin-CDR3H-coil-Herceptin up-regulated gene expression in liver and hypothalamus at multiple time points by quantitative PCR in mice treated with the fusion protein ( Table 2).…”
Section: Resultsmentioning
confidence: 99%